Pengolahan Katsu Semur Jengkol (Archidendron Pauciflorum) pada Kedai Bikin Nagih - Sovia Nafsiatul Muthmainnah; Suryana Suryana (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
The research conducted on Katsu Semur Jengkol aims to add a new menu variation for burgers at Kedai Bikin Nagih. Generally, Jengkol is only prepared as Balado Jengkol, Rendang Jengkol, and Semur Jengkol. This study aims to assess the preference level of the panelists based on five attributes: appearance, color, texture, aroma, and taste, as well as recipe standards and business analysis. The method used in this research is research and development, involving a series of experiments and developments using hedonic scale scoring tests with 25 panelists. The summary results of the main taste preference test regarding the appearance, color, texture, aroma, and taste of Katsu Semur Jengkol show that 76.6% of the panelists liked it very much, while 22.4% liked it. Based on the research conducted, the standard recipe includes 300g of jengkol, 100g of chicken, 1 egg, 20g of flour, 20g of breadcrumbs, 5g of flavoring, 2g of salt, 30g of onion, 5g of green onion, 2g of pepper, 1ml of jengkol essence, 14g of red onion, 7g of garlic, 5g of candlenut, 8g of red chili, 0.2mg of nutmeg, 5g of flavoring, 6g of sugar, 15g of sweet soy sauce, 2g of salt, 100ml of water, 100g of flour, and 150g of breadcrumbs. The business analysis calculations indicate a cost price of Rp.1,176, a selling price of Rp.4,000, and a food cost of 30.59%. The break-even point is reached with sales of 600 pieces, and a profit of Rp.5,000,000 per month can be achieved with sales of 2,600 pieces. It is recommended that future researchers focus on innovation, especially in the culinary field, by utilizing other raw materials available in our surroundings.